Politik Hukum Adat di Indonesia Era Kolonial: Akomodasi, Penetrasi dan Resistensi - Ibi Satibi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
One of the concern of scholars regarding the politics of customary law in Indonesia at the colonial period is the encounter of three legal traditions, customary law, Islamic law and colonial law. The three of them not only had unique and different characteristics from each other, but also showed an intense struggle with tension and sometimes conflict among Indonesia society at the time. This paper seeks to describe the political dimension of customary law, as one of the three legal traditions that struggles against the strengths of the other two legal traditions. By utilizing the theory of continuity and change, this paper finds that the politics of customary law during the colonial period provided continuity the the climate of colonial penetration in the field of law. This condition has an impact on the marginalization of Islamic law which has long been inherent in Muslim society. However, at the same time the colonial government strengthened customary law as part of positive law through a legal codivication policy. This article confirms that the politics of customary law in the colonial period showed a systematic pattern toward division and change of legal society, between supporters of customary law and those who consistently adhered to Islamic law.